Phos - The Official ATHENS 2004 Olympic Greek Album - Theodorakis, Mikis (EMI, 2004)
The record that most closely represents the spirit of Greece, the land that gave birth to the Olympic Games, is "Phos". This aims, as its title suggests, to shed the light of the universal ideals that originated in Greece. The album’s 18 songs by Mikis Theodorakis, with the participation of 15 leading musicians, were chosen to put across the ardour and spirituality of the Greek soul to the whole world. [www.athens2004.com]